USING PLAN (PREDICT,LOCATE, ADD, NOTE) STRATEGY IN TEACHING READING DESCRIPTIVE TEXT - Mike Amelia (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2018)
The aim of this study was to determine the effect of  PLAN (Predict, Locate, Add, and Note) Strategy in Teaching Reading Descriptive text to Junior High School at SMP N 1 Bukit Sundi. This  research used experiment research design  that consist of two groups as the sample groups. They were: an experimental class that used  PLAN Strategy and the other was control class, used discovery learning strategy. The population of this research were eight grade students of  SMP N 1 Bukit Sundi that have learn descriptive text. The samples of this research were class VIII.E as experimental class (20 Students) and class VIII.D as control class (20 students. Instruments that used in collecting the data was reading test. The result of the research showed that PLAN trategy gave possitive effect on students’ reading comprehension of descriptive text. It could be seen from mean scores of students’ test at experimental class was higher than mean scores of students’ reading test at controll class. This strategy gave more challenging activites and develop students’ autonomy and made students’ easier in comprehending desriptive text. Keyword: PLAN, Reading, Descriptive Text PENGGUNAAN STRATEGI PLAN (PREDICT, LOCATE, ADD , NOTE) DALAM PENGAJARAN TEKS DESCRIPTIFAbstrakTujuan dari penelitian ini adalah untuk melihat pengaruh dari penggunaan strategi PLAN (Predict, Locate, Add, Note) dalam pengajaran reading teks deskriptiv di SMP N 1 Bukit Sundi. Penelitian ini merupkan penelitian experimen yang terdiri dari dua kelas sampel. Kelas eperiment menggunakan strategi PLAN  dan kelas kontrol menggunakan strategi pembelajaran discovering. Populasi dari penelitin ini adalah kelas delapan SMP N 1 Bukit Sundi yang telah mempelajari teks deskriptiv. Sampel dari penelitian ini adalah kelas VIII.E  (20 orang) dan kelas VIII.D  sebagai kelas kontrol (20 orang). Instrumen yang digunakan dalam mengumpulkan data adalah tes reading. Hasil penelitian ini menunjukkan bahwa strategi PLAN memberikan efek positif terhadap kemampuan siswa dalam memahami teks descriptif. Hal ini dapat dilihat dari mean score hasil tes reading kelas experimen lebih tinggi dibandingkan dengan kelas control. Strategi ini memberikan aktivitas yang dapat meningkatkan dan membuat siswa dapat memahami teks descriptif lebih mudah.Kata Kunci: PLAN, Reading, Descriptive Text